Recent improvements in marathon run times are likely technological, not physiological - Muniz-Pardos, B.; Sutehall, S.; Angeloudis, K.; Guppy, F. M.; Bosch, A.; Pitsiladis, Y. (Sports Medicine, 2021)
Every women`s and men`s world records from 5 km to the marathon has been broken since the introduction of carbon fibre plate (CFP) shoes in 2016. This step-wise increase in performance coincides with recent advancements in shoe technology that increase the elastic properties of the shoe thereby reducing the energy cost of running. The latest CFP shoes are acknowledged to increase running economy by more than 4%, corresponding to a greater than 2% improvement in performance/run time. The recently modified rules governing competition shoes for elite athletes, announced by World Athletics, that includes sole thickness must not exceed 40 mm and must not contain more than one rigid embedded plate, appear contrary to the true essence and credibility of sport as access to this performance-defining technology becomes the primary differentiator of sporting performance in elite athletes. This is a particular problem in sports such as athletics where the primary sponsor of the athlete is very often a footwear manufacturing company. The postponement of the 2020 Summer Olympics provides a unique opportunity for reflection by the world of sport and time to commission an independent review to evaluate the impact of technology on the integrity of sporting competition. A potential solution to solve this issue can involve the reduction of the stack height of a shoe to 20 mm. This simple and practical solution would prevent shoe technology from having too large an impact on the energy cost of running and, therefore, determining the performance outcome.